The Development of Airport Identity of Chiang Mai International Airport Through the Creation of Airport Sense of Place - Anantakoon, Prapop; Choibamroong , Therdchai (Rajapark Journal, 2024)
This research aimed to 1) study the successful and challenging factors of airports of Thailand Public Company Limited in developing airport identity of Chiang Mai International Airport, Thailand; 2) identify the perception of airport stakeholders towards the implementation of airport identity of Chiang Mai International Airport, Thailand; and 3) propose a framework in planning and development of airport identity of Airports of Thailand Public Company Limited. The sample was 31 interviewees. They were selected by purposive sampling and snowball sampling. The instrument for collecting data was an in-depth interview. Analysis of data by Content Analysis. The research results were found as follows; 1) Airports of Thailand Public Company Limited had a Thailand Gateway Policy to develop the airport identity of six international airports; 2) Airport stakeholders had a perceived value of the airport sense of place; and 3) propose a development framework to create a successful airport identity consisting of airport strategy, airport design, airport attributes, airport revenue management, and airport community engagement.